ICT COMPETENCES FOR THE NEXT GENERATION OF TEACHERS - DOSTÁL, Jiří (Trends in education, 2009)
All teachers need to be prepared to provide ICT technology-supported learning opportunities for their students. Being prepared to use technology and knowing how that technology can support student learning have become integral skills in every teacher's professional repertoire. Teachers need to be prepared to empower students with the advantages technology can bring.
Keywords: ICT competences; information literacy; computer literacy; information education; education.